Hybrid-specific nutrient and water use of maize on chernozem soil - Karancsi, Lajos (Acta Agraria Debreceniensis, 2013)
The field research was set up on chernozem soil at the Látókép AGTC KIT research area of the University of Debrecen. The study focused on yield, water utilization, nutrient reaction and the amount of yield per kg fertilizer of corn hybrid NX 47279 in 2011 and 2012. Based on the yield results it can be concluded that the largest yield in 2011 was 15 963 kg ha-1 at level N120+PK, while in 2012, the maximum yield amounted to 14 972 kg ha-1 at level N90+PK. Surplus yield per kg fertilizer proved that in 2011 level N30+PK resulted in the highest surplus yield (42.3 kg kg-1) compared to the control treatment. In 2012, yield growth was 18.0 kg kg-1 compared to the control treatment. We measured at level N60+PK 17,5 kg kg-1 compared to at level N30+PK, at the N90+PK 17,7 kg kg-1 compared to at level N60+PK. level N30+PK kg kg-1, 17.5 kg kg-1 at level N60+PK and 17.7 kg kg-1 at level N90+PK compared to the control treatment.Results of the regression analysis showed that the amount of nitrogen fertilizer was 117 kg ha-1 in 2011 and 111 kg ha-1 in 2012 in order to reach maximum yield. Doses of fertilizers above the amounts previously mentioned resulted in yield decrease. Our results indicated that in the drought year of 2012 the hybrid used available water more efficiently than in 2011. The hybrid produced 59 kg ha-1 yield in 2012 and 51.9 kg ha-1 in 2011 at an optimum nutrition level.